PETA VIRTUAL 3D PERPUSTAKAAN UNIVERSITAS LAMPUNG - Irwan Adi Pribadi; Yunda Heningtyas; Arief Laksana (Jurnal Pepadun, 2022)
The Lampung University Library building has enough rooms to make it difficult for students to find the intended room. Information about the layout of the building is very inefficient and difficult for students to understand because they still use conventional maps. This research is intended to make it easier for students and the people of the University of Lampung to provide information on the layout of the building that is being addressed. By making a replica of the Lampung University Library Building in the form of a 3D Virtual Map. The system development method used in this research is the Multimedia Development Life Cycle (MDLC) which consists of 6 stages, namely concept, design, material collection, manufacture, testing and distribution. The 3D Virtual Map application for the Lampung University Library Building has been developed using desktop-based Virtual Reality technology. The creation of a 3D Virtual Library Map is done with SketchUp and Unity3D. Black box testing consists of testing the menu functionality in the application. The results of testing the functionality of the application menu show that all functions in the application can run well according to the input given.